Pacemaking Property of RVLM Presympathetic Neurons - Accorsi-Mendonça, Daniela; da Silva, Melina P.; Souza, George M. P. R.; Lima-Silveira, Ludmila; Karlen-Amarante, Marlusa; Amorim, Mateus R.; Almado, Carlos E. L.; Moraes, Davi J. A.; Machado, Benedito H. (Frontiers in Physiology, 2016)
Despite several studies describing the electrophysiological properties of RVLM presympathetic neurons, there is no consensus in the literature about their pacemaking property, mainly due to different experimental approaches used for recordings of neuronal intrinsic properties. In this review we are presenting a historical retrospective about the pioneering studies and their controversies on the intrinsic electrophysiological property of auto-depolarization of these cells in conjunction with recent studies from our laboratory documenting that RVLM presympathetic neurons present pacemaking capacity. We also discuss whether increased sympathetic activity observed in animal models of neurogenic hypertension (CIH and SHR) are dependent on changes in the intrinsic electrophysiological properties of these cells or due to changes in modulatory inputs from neurons of the respiratory network. We also highlight the key role of INaP as the major current contributing to the pacemaking property of RVLM presympathetic neurons.